Short-horizon acceleration-predictive control for reducing lateral seismic inertia forces of inelastic frame structures using semi-active fluid viscous dampers - Shmerling, Assaf; Gerdts, Matthias (Computers & structures, 2023)
•Exploitation of semi-active fluid dampers' full potential in inelastic frame structures.•Using semi-active fluid dampers to reduce seismic inertia forces.•Practical closed-loop control of total acceleration as simulated feedback.•Modified Kalman filter scheme that bypasses system uncertainties.•Implementation of short-horizon predictive control in structural design problem. Semi-active control systems effectively improve the resilience of civil structures when subject to dynamic vibrations due to their ability to change their damping properties. In the case of semi-active fluid viscous dampers (SAFVD), the damping coefficient quantity varies according to the tradeoff between the need to increase the energy dissipation capabilities (i.e., increasing the damping coefficient) and the need to decrease the applied shear forces (i.e., reducing the damping coefficient). The operation of a SAFVD device is similar to that of a passive fluid viscous damper except that, based on the status of the control valve, it can deliver damping at two distinct levels (two-stage) or over a wide range between an upper and lower bound (continuously adjustable). This paper employs a continuously adjustable SAFVD assembly and develops its optimal command voltage change at each time step, which regulates the valve that determines the fluid passing through the external path. The control strategy uses total acceleration measurement as the system's closed-loop feedback and utilizes the Kalman filter model to predict the sequential acceleration reading to cater to time delays. The solution derives from a short‐horizon problem whose objective is reducing the difference between the lateral seismic inertia forces and the SAFVD forces, thus, mitigating the columns’ resisting forces. The case study presented in this paper showcases the effectiveness of the SAFVDs in improving the inelastic earthquake response of a 10-story frame structure.